Dealing with unlawful sources of funds among Islamic banks in Malaysia: the practitioners’ perspectives - Hj Ibrahim, Badruddin; Che Mohd Salleh, Marhanum; Mohd, Azizah; Laeba, Muhammad (Emerald Publishing Limited, 2019)
This chapter offers a practitioners’ perspective on how Islamic banks in Malaysia deal with unlawful sources of funds. Specifically, it investigates the practice of Islamic banks in Malaysia in dealing with funds that originate from unlawful sources such as accepting deposits for safe-keeping and investment and providing financial facilities to customers whose incomes come from unlawful sources. This is regardless of whether the sources of fund are wholly unlawful or there is a mix of lawful and unlawful sources. A quantitative methodology is adopted to collect data from selected industry practitioners who are directly involved with Islamic banks, mainly officers of Sharīʿah departments, members of Sharīʿah committees and other stakeholders of Islamic banks. Based on a simple descriptive analysis, it is found that majority of the respondents opine that when the sources of funds are deemed unlawful, the bank cannot accept such deposits, investments or give financing to a customer if he or she is known to possess unlawful sources of funds. With respect to the mixed sources of funds or activities, that is, lawful and unlawful, the bank should not be prevented from receiving the funds either for safe-keeping, investment or payment of financing. The study also finds that banks have the right to investigate the sources of funds of the customers whether they are derived from Sharīʿah compliant, non-Sharīʿah compliant or mixed sources as part of the general due diligence implemented by such banks.